Narrator i czas w opowiadaniach Jorge Luisa Borgesa - MARIA BIELAWKA (Stylistyka, 2021)
The paper consists of two parts. The former is an attempt at showing the main idealistic theses related to time as presented by narrators in the short stories, especially in so-called metaphysical stories of Jorge Luis Borges, the outstanding Latin-American author. The theses are as follows: 1. The world, as well as time, are constituted by God; they emerge ex Divine aeternitate. 2. Time, as well as the so-called “real world”, are not fully real; they are phenomena. 3. The time of the materiał level of the world differs from the subjec- tive, psychic time. 4. Time is a necessary condition of entering the path of self-perfecting. 5. Even God cannot change past events, but He may allow us to change their interpreta- tion, or to “take the spell off”, due to personal expiation, among other things. The same concept of time is also expressed in Borges’ two essays: History of Eternity and New Re- futation of Time.The second part of the paper is devoted to the stylistic means involved in the presenta- tion of time. A certain vagueness and phenomenality of time and the world in Borges’ short stories are achieved by the following two means: mixing the levels of wakefulness and dreaming, and introducing the fictional, non-existing objects into the domain of the presented world. The specific aesthetic effects are obtained primarily by filling in the for- mal “scheme of time” with concrete events and by applying the “double” narration met- hod. In consequence, the double perspective of time is achieved.